NEGOSIASI DAN KONTRAK DAGANG DALAM PERDAGANGAN INTERNASIONAL ” EXPORT’ DI Fa. ARI - Ni Made Rai Sukmawati; I Made Budiasa (Soshum: Jurnal Sosial dan Humaniora, 2013)
Trading activities both domestic or foreign trade needs a special strategy and technique in order to achieve their maximum target. The global crisis in particular the inclusion of Asian China Free Trade Agreement (ACFTA) market raise strongly effect for trading company engaged in export trade. This evidenced by the decrease in sales turnover of previous years. The company deems it necessary to conduct the analysis to finds a solution, and able to keep their presence and survive in running the company by reviewing the price and negotiation techniques by using SWOT analysis. The company should improve their quality and create an innovative product as the market needs. Besides that, hope to remain competitive in the international market with their competitors countries such as Thailand, China, Vietnam, India, and other countries. With the SWOT analysis is expected the company can take a decision for increasing their sales. For increasing sales the company also needs to promoting their products and has a negotiation technique that they can attract new customers.